Applications of fluorescent materials in the detection of alkaline phosphatase activity. Issue 2 (13th August 2020) - Guo, Jiantao; Yu, Hongbo; Cui, Tingting
Abstract: Alkaline phosphatase (ALP) is important in the diagnosis of many diseases. Because ALP is used to detect biomarkers for many diseases, many researchers conduct investigations to develop ALP detection strategies. The use of fluorescent material has attracted attention because of the technique's high sensitivity and the low sample volume required. Herein, we review and discuss the working mechanisms and advantages of four main categories:DNA fluorescent probes, molecular fluorescent probes, chemical coordination‐based probes, and nanoparticle probes. Development prospects and trends are also discussed.